2023
DOI: 10.3390/brainsci13040593
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia Is Associated with the Acute Kidney Injury in Traumatic Brain Injury Patients: A Pilot Study

Abstract: Background: Acute kidney injury (AKI) commonly develops among traumatic brain injury (TBI) patients and causes poorer outcomes. We perform this study to explore the relationship between serum magnesium and the risk of AKI among TBI. Methods: TBI patients recorded in the Medical Information Mart for Intensive Care-III database were eligible for this research. The restricted cubic spline (RCS) was utilized to fit the correlation between serum magnesium level and the AKI. Univariate and subsequent multivariate lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Our results demonstrated that both lower serum magnesium levels (≤1.7 mg/dL) at admission and greater changes in magnesium levels during hospitalization (CV >10%) were linked to an increased risk of AKI. Recently, Liu et al [15] conducted a study to explore the factors associated with the risk of AKI in patients with TBI and showed that hypomagnesemia was associated with a higher risk of AKI. However, their study did not analyze the effect of magnesium changes on AKI risk nor did it analyze the effect of magnesium on AKI risk in different patients (e.g., GCS scores).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results demonstrated that both lower serum magnesium levels (≤1.7 mg/dL) at admission and greater changes in magnesium levels during hospitalization (CV >10%) were linked to an increased risk of AKI. Recently, Liu et al [15] conducted a study to explore the factors associated with the risk of AKI in patients with TBI and showed that hypomagnesemia was associated with a higher risk of AKI. However, their study did not analyze the effect of magnesium changes on AKI risk nor did it analyze the effect of magnesium on AKI risk in different patients (e.g., GCS scores).…”
Section: Discussionmentioning
confidence: 99%
“…Several possible mechanisms for the effect of serum magnesium levels on AKI risk have been proposed. Magnesium is an important modulator of vascular tone and enhances renal vasodilatation by releasing endogenous vasodilators such as nitric oxide, adenosine, and prostaglandins, as well as by forming competition with calcium ions (Ca + ) [15,30]. Lower magnesium levels are associated with inflammation, as magnesium deficiency opens calcium channels, upregulates pro-inflammatory cytokines, and activates nuclear factor-κB, leading to inflammation [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation